Inequality in China An Overview - Knight, John (The World Bank, 2013)
This paper provides an overview of research on income inequality in China over the period of economic reform. It presents the results of two main sources of evidence on income inequality and, assisted by various decompositions, explains the reasons income inequality has increased rapidly and the Gini coefficient is now almost 0.5. This paper evaluates the degree of income inequality from the perspectives of people's subjective well-being and government concerns. It poses the following question: has income inequality peaked? It also discusses the policy implications of the analysis. The concluding comments of this paper propose a research agenda and suggest possible lessons from China's experience that may be useful for other developing countries